IMPROVING STUDENTS' LISTENING SKILL THROUGH PODCASTS - Astuti, Ayu Viviyani; Syam, Ummi Khaerati; Daddi, Herlina (English Language Teaching Methodology, 2024)
The aims of this research was to describe and find out; (1) The implementation of the podcasts in improving students’ listening skill; (2) The improvement of students listening skill through podcasts. The method that used in this research was Classroom Action Research (CAR). This study was conducted following Kemmis and MacTaggart action research procedures; planning, acting, observing, and reflecting. This research carried out in two cycles. The cycle consisted 8 meetings. Most of the students got the good scores. The score of Minimum Mastery Criterion (KKM) was 75. In the first listening test there was 4 students who got points of over 75, that is 20%. In the second listening test there was 6 students who got points over 75, the presentage is 45%. It was increased by 10%. Afterwards, in the third listening test there was 16 students got points over 75. Next, there was improvement 45% for the second listening test, 80% from the first listening test to the third test. The class condition during teaching learning process was good and also got the positive response from the English teacher and students towards the action. To sum up, listening English podcasts can improve students’ listening skill.